The influence of financial performance and macroeconomic on financing risk in Islamic banks - Dita Putri Angraini; Heri Sudarsono; Sella Fitri Anindita (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: The aim of this research is to identify the influence of microeconomic and macroeconomic variables toward non-performing financing of Islamic Commercial Banks in Indonesia.Design/Methodology/Approch: Microeconomic variables include CAR, FDR, OEOI, ROA, while macroeconomic variables include IPI, BI Rate, Inflation and SBIS for the period of 2015 to 2019. The data analysis method in this study is Auto-Regressive Distributed Lag (ARDL) using EViews 10 tool which can analyze the relationship between independent and dependent variables in the long-term and the short-term.Findings This study shows that CAR has a positive and insignificant effect on NPF. Furthermore, BOPO, ROA, BI Rate have a significant positive effect on NPF, but FDR, inflation and SBIS have a significant negative effect on NPF. In the long-term, CAR, IPI and SBIS have a negative and insignificant effect on NPF, but BI Rate has a positive and insignificant effect. Suggestion in this research is to solve better research, so further research should be carried out by including a longer period of time.Practical implications: Islamic Bank Directors need to pay attention to the movement of BOPO and ROA which tend to consistently have a positive effect on the NPF level.Originality/Value: This study presents the long-term and the short-term relationships of specific Islamic banking variables and macroeconomic variables on NPF in Indonesia.